Floristic diversity of vascular plants in the Mimouna Forest (north-western Algeria) - Saidi, Abdelmoumene; Keifa, Abdelkrim (Biodiversity: Research and Conservation, 2024)
In arid and semi-arid areas, wild vegetation is a very important natural resource and provides various ecosystem services, such as environmental adjustment functions. It is therefore important to manage and protect plant diversity in these areas. We investigated the Mimouna Forest in the Algerian Saida Province, characterized by a Mediterranean-type climate with maximum average monthly temperature of 27.1°C, minimum of 8.3°C and annual rainfall of 345 mm. We described and analysed the species diversity of vascular plants in this area. The floristic inventory was carried out using a subjective sampling method. This allowed us to identify 93 species belonging to 80 genera and 33 botanical families. The major families were the Asteraceae (16%) and Poaceae (14%). The analysis of plant life-forms showed the dominance of therophytes (36%) and hemicryptophytes (28%). On the phytogeographic level, the prevailing chorological elements were of Mediterranean affinity (54% in total). Endemic taxa accounted for 9% of the flora. The Shannon index was moderately high (3.62) and 13% of the recorded species were rare, including 5 protected by Algerian law.